METAVERSE DALAM PENDIDIKAN AGAMA ISLAM: EKSPLORASI MEDIA VIRTUAL UNTUK PENGUATAN NILAI-NILAI SPIRITUAL - Dimyati , Muhamad (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
The advancement of digital technology, particularly the metaverse, has brought significant changes to various sectors, including education. Islamic Religious Education (IRE), as an integral part of character and spiritual development, faces both challenges and opportunities in navigating this transformation. This study aims to explore the potential of metaverse-based virtual media in strengthening spiritual values within the context of IRE learning. A qualitative exploratory method was employed, using literature review and in-depth interviews with educators and developers of educational metaverse technologies. The findings indicate that the metaverse can serve as an alternative medium that is interactive, immersive, and participatory for delivering religious content, such as virtual worship practices, simulations of Islamic history, and learning moral values. The use of avatars, virtual classrooms, and simulated environments in the metaverse enhances students’ emotional and spiritual engagement, providing a deeper and more personal learning experience. However, ethical and technical challenges—such as content control, digital security, and the need for religious digital literacy—must be addressed prudently. This study recommends a gradual integration of the metaverse into the IRE curriculum, accompanied by the development of educators’ digital competencies and a regulatory framework rooted in Islamic values. These findings are expected to serve as an innovative foundation for the development of adaptive religious education strategies in the era of Industry 5.0 and digital society.